Respuesta :

The product is [tex]60-42 \sqrt{ 5}[/tex].

Solution:

Express the product of [tex]3 \sqrt{20}(2 \sqrt{5}-7)[/tex] in simplest radical form.

Given expression:

[tex]3 \sqrt{20}(2 \sqrt{5}-7)[/tex]

To simplify the expression:

[tex]3 \sqrt{20}(2 \sqrt{5}-7)=3 \sqrt{4\times 5}(2 \sqrt{5}-7)[/tex]

                        [tex]=3 \sqrt{2^2\times 5}(2 \sqrt{5}-7)[/tex]

                        [tex]=3\times 2 \sqrt{ 5}(2 \sqrt{5}-7)[/tex]

                        [tex]=6 \sqrt{ 5}(2 \sqrt{5}-7)[/tex]

Multiply 6√5 into inside the bracket.

                        [tex]=6 \sqrt{ 5}\times 2\sqrt{5}-6 \sqrt{ 5}\times 7[/tex]

We know that √5 × √5 = 5

                        [tex]=12\times 5-42 \sqrt{ 5}[/tex]

                        [tex]=60-42 \sqrt{ 5}[/tex]

[tex]3 \sqrt{20}(2 \sqrt{5}-7)=60-42 \sqrt{ 5}[/tex]

Hence the product is [tex]60-42 \sqrt{ 5}[/tex].

ACCESS MORE